Toothbrush bristles
Patent Information
- Application Number
- JP2025057711
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本発明によれば、高比重の無機粒子を含有させることで毛材の比重を高め、かけた応力を効率よく毛先に伝達させ、優れた清掃性を具備し、屈曲回復率を落とさず、毛開き耐久性の高さも両立した歯ブラシ用毛材および歯ブラシが得られる。
Smart Images

Figure 2026165364000001
Abstract
Description
Technical Field
[0001] The present invention relates to a bristle material for toothbrushes.
Background Art
[0002] In recent years, electric toothbrushes in which the brush portion performs high-speed reciprocating motion, high-speed rotation or high-speed reversal driven by motor driving force have been becoming popular in place of conventional toothbrushes, due to the advantages of excellent tooth surface cleanability and no burden felt on the hand even after brushing for a long time.
[0003] As for the form of bristles used for such electric toothbrush bristles, those obtained only by chamfering the end faces of cut bristles and rounding the bristle tips were common, but recently, for the purpose of further improving cleaning performance, various forms such as a spherical tip type, a tapered type, and a split tip type have been adopted. Among them, bristles with tapered bristle tips and bristles with split tips have been recognized as effective, and have begun to be used in the electric toothbrush field as well.
[0004] As specific examples of such products, there are known a toothbrush bristle in which a chemically sharpened tapered portion is formed at the tip of a bristle made of synthetic resin monofilament (see Patent Document 1), and a toothbrush bristle in which the ratio of the tapered portion at the filament tip to the total length of the bristle is specified (see Patent Document 2). However, when these bristles with tapered bristle tips are used in electric toothbrushes, although the inter-tooth insertability is excellent, the bristle stiffness becomes soft due to the tapering process, so the force applied to the handle portion during brushing is attenuated by the deflection of the bristle material, making it difficult for stress to be transmitted to the bristle tips. Therefore, there is a problem that it is necessary to finely control the applied stress and the sliding method, which ends up relying on the individual's brushing skill.
[0005] Furthermore, as described in Patent Document 3, there is a technology that provides high cleaning performance with less force by creating irregularities on the surface of the thread, but there is a problem that dirt can get into the recesses of the thread, making the toothbrush bristles unsanitary. Also, as described in Patent Document 4, there is a technology that can be expected to provide high cleaning performance by increasing the specific gravity and kinetic energy of a composite fiber with a core-sheath structure by kneading high-density fine particles into the core component of the thread. However, if the high-density portion is solidified into the core component, the core component becomes brittle, making the bristles prone to breakage and preventing durability from being maintained. In addition, there is a problem that the core component and the sheath component do not mix well, causing the bristles to split during brushing. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 6-141923 [Patent Document 2] Japanese Patent Application Publication No. 2001-169828 [Patent Document 3] Patent No. 4807760 [Patent Document 4] Japanese Patent Publication No. 2000-265332 [Overview of the project] [Problems that the invention aims to solve]
[0007] The objective of this invention is to provide a toothbrush bristle material that can efficiently transmit stress during brushing, maintain high cleaning performance with less force and without relying on brushing technique, and is also highly durable. [Means for solving the problem]
[0008] This invention was achieved as a result of studies aimed at solving the above-mentioned problems. [1] Toothbrush bristles consisting of monofilaments having a specific gravity of 1.40 to 2.03, a fineness of 350 dtex to 470 dtex, and a bending recovery rate of 45% or more. [2] The toothbrush bristle material according to [1], wherein the monofilament is a thermoplastic resin containing 10% by mass or more and 50% by mass or less of inorganic particles. [3] The toothbrush bristles according to [1] or [2], wherein the thermoplastic resin is a polyester resin or a polyamide resin. [4] The toothbrush bristle material according to any one of [1] to [3], wherein the inorganic particles are inorganic particles with a weight-average particle size of 5 μm or less. [5] A toothbrush using at least part of the toothbrush bristles described in any of [1] to [4] above. [Effects of the Invention]
[0009] According to the present invention, by incorporating high-density inorganic particles, the specific gravity of the bristles is increased, the applied stress is efficiently transmitted to the bristle tips, and a toothbrush bristle material and toothbrush can be obtained that have excellent cleaning properties, maintain a high bending recovery rate, and have high durability against bristle spreading. [Modes for carrying out the invention]
[0010] The present invention will be described in detail below.
[0011] The toothbrush bristles of the present invention consist of monofilaments having a specific gravity of 1.40 to 2.03, a fineness of 350 to 470 dtex, and a bending recovery rate of 45% or more.
[0012] If the specific gravity of the monofilament is less than 1.40, sufficient plaque removal cannot be obtained. On the other hand, if the specific gravity exceeds 2.03, stress is not efficiently transmitted to the bristles, resulting in poor plaque removal, reduced strength, and a brittle monofilament that is easily broken by bending. From this viewpoint, the specific gravity of the monofilament is preferably between 1.40 and 1.66.
[0013] To adjust the specific gravity of the monofilament to the specified range, it is possible to use a thermoplastic resin with a specific gravity within the above range, as described later, or to adjust it by adding inorganic particles as a specific gravity adjusting agent to the thermoplastic resin. The inorganic particles used in this case will be described later. Adding inorganic particles improves the cleaning performance as a toothbrush, so the method of adding inorganic particles as described above is preferred.
[0014] The toothbrush bristles of the present invention consist of monofilaments with a fineness of 350 dtex or more and 470 dtex or less. If the fineness of the monofilaments is less than 350 dtex, sufficient plaque removal cannot be obtained. On the other hand, if the fineness exceeds 470 dtex, stress is not efficiently transmitted to the bristle tip, resulting in poor plaque removal, as well as reduced strength, making the monofilaments brittle and prone to breakage by bending. From this viewpoint, a fineness of 350 to 470 dtex is preferred for the monofilaments.
[0015] The toothbrush bristles of the present invention consist of monofilaments with a bending recovery rate of 45% or more. If the bending recovery rate of the monofilaments is less than 45%, the bristle breakage resistance will be insufficient, and the lifespan of the toothbrush will be shortened. From this viewpoint, a bending recovery rate of 60% or more is preferable for the monofilaments. Furthermore, a bending recovery rate of 100% or less is preferable for the monofilaments.
[0016] Examples of thermoplastic resins that constitute the bristles of the toothbrush of the present invention include polyamide resins and their copolymers such as nylon 6, nylon 66, nylon 610, nylon 612, and nylon 6 / 66 copolymer; polyester resins and their copolymers such as polyethylene terephthalate (hereinafter referred to as PET), polybutylene terephthalate (hereinafter referred to as PBT), polytrimethylene terephthalate (hereinafter referred to as PTT), polyethylene naphthalate, and polycyclohexanedimethylene terephthalate; fluororesins such as polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer; polyolefin resins such as polyethylene and polypropylene; polyphenylene sulfide resin (hereinafter referred to as PPS); and polyacetal resin. However, from the viewpoint of strength, toughness, and heat resistance, polyester resins represented by PET, PBT, and PTT, and polyamide resins represented by nylon 610 are particularly preferred, and PBT is even more preferred.
[0017] In the present invention, inorganic particles may be included in the thermoplastic resin. When inorganic particles are included, examples of materials for the inorganic particles include glass beads, talc, silica, mica, calcium carbonate, magnesium hydroxide, alumina, zinc oxide, magnesium oxide, magnesium hydroxide, silica alumina, titanium oxide, calcium oxide, calcium silicate, molybdenum sulfide, antimony oxide, clay, diatomaceous earth, calcium sulfate, calcium sulfite, iron oxide, barium sulfate, magnesium carbonate, basic magnesium carbonate, dolomide, montmorillonite, bentonite, iron powder, lead powder, zinc powder, aluminum powder, carbon black, and the like. Among these, barium sulfate or calcium carbonate is particularly preferred in terms of dispersibility in the thermoplastic resin and cost, and barium sulfate is even more preferred.
[0018] The content ratio of the inorganic particles in the thermoplastic resin is 10 mass% or more and 50 mass% or less, more preferably 10 mass% or more and 30 mass% or less. If the content is below the above range, a sufficient specific gravity may not be obtained, and if the content exceeds the above range, the strength of the monofilament may decrease, the monofilament may become brittle, or it may easily break when bent.
[0019] When inorganic particles are contained, the weight average particle diameter of the inorganic particles in the thermoplastic resin is preferably 5 μm or less, particularly more preferably 2 μm or less, and further preferably 0.6 μm or less. If the weight average particle diameter exceeds the above range, the strength of the monofilament may decrease, the particles may detach during use, or the detergency may deteriorate over time. In addition, fouling of the spinneret during spinning may occur, which may cause variations in physical properties. The lower limit of the weight average particle diameter is not particularly limited, but is preferably 0.05 μm or more.
[0020] Next, the method for producing the bristle material for brushes of the present invention will be described.
[0021] The method for producing the bristle material for brushes of the present invention does not require any special method, and a known spinning method can be applied. For example, a thermoplastic resin is melt-extruded using a kneading extruder such as an extruder, or a melt spinning machine of the pressure melter type, followed by cooling and solidification, hot drawing, and heat setting to form a synthetic resin monofilament, which is then cut to a required length.
[0022] The cross-sectional shape of the bristle material for brushes of the present invention is not particularly limited, and may be a flat shape other than a circle, a square, a half-moon shape, a fan shape, a triangular shape, a polygon with five or more angles, a multi-lobed shape, a dog-bone shape, a cocoon shape, or the like, and a hollow portion may be provided. It can also be used as one component of a composite yarn.
[0023] Further, in order to taper the tip of the synthetic resin monofilament, the tapered shape can be easily formed by immersing the monofilament in caustic soda to dissolve the tip portion.
[0024] Furthermore, the brush bristles of the present invention can be used not only in oral care products such as toothbrushes and interdental brushes, but also in hairbrushes, body brushes, cleaning brushes, and cosmetic brushes. [Examples]
[0025] The brush bristles of the present invention will be described in more detail below based on the examples provided, but the present invention is not limited to these examples.
[0026] The various characteristic values of the brush bristles were measured by creating a toothbrush with bristles planted in a head having 1.5 mm in diameter and 8 rows and 4 columns of bristle holes, and measuring them according to the following method.
[0027] Furthermore, the cleanability and durability of the examples were evaluated according to the following methods.
[0028] [Fineness] The definition in JIS L 1013:2010 was followed. Specifically, the sample, taken in skein form, was left in a temperature and humidity controlled chamber at 20°C and 65%RH for 24 hours. Then, four 50cm length samples were taken, their masses were measured, and the total mass was used as the sample mass. The mass was then calculated using the following formula. The measurement was performed with n=1.
[0029] Fineness (dtex) = Mass of sample (mg) × 5000.
[0030] [specific gravity] Measurements were performed according to the JIS K 7112:1999-B method (pycnometer method). Distilled water at 25°C ± 0.1°C was used as the solution. The mass of the pycnometer (Wa), the mass of the pycnometer + sample (Wb), the mass of the pycnometer + sample + solution up to the mark (Wc), and the mass of the pycnometer + solution up to the mark (Wd) were measured. The density of distilled water at 25°C is 0.99704 g / cm³. 3 It was calculated using the following formula. The measurement was performed with n=1.
[0031] The formula is (Wb-Wa)×0.99704 / (Wb-Wa-Wc+Wd).
[0032] [Bending recovery rate] A sample is created by forming a loop with a thread approximately 260 mm long, creating a chain shape, and tying the ends together. One loop is suspended from a pin on a bending table, and a load equal to half the target fineness calculated using the following formula is applied to the lower loop for 3 minutes. After that, the thread is cut approximately 30 mm from the bend and left lying horizontally.
[0033] After leaving it in that state for 60 minutes, the opening angle was measured with a protractor and defined as the bending recovery rate. The measurement was performed with n=2.
[0034] Target fineness = 8799 × sample diameter 2 (mm)
[0035] [Cleanability] A simulated tooth model was created by creating a 1.0 mm groove-like gap between two acrylic plates. A simulated tooth model was pre-treated with a dental occlusion check spray to deposit visible plaque. Then, an electric toothbrush manufactured from an electric toothbrush bristle was used to brush the model for 3 minutes. After brushing, the area cleaned was measured, and the percentage of the area cleaned relative to the previously deposited visible plaque was calculated. Measurements were performed with n=5, and the average value was evaluated according to the following criteria.
[0036] ◎; Spray removal rate (%) is 80.0% or higher ○; Spray removal rate (%) is 70.0% or higher △; Spray removal rate (%) is 60.0% or higher ×; The removal rate (%) of the spray is less than 60.0%.
[0037] [Durability] Using the artificial tooth model described above for cleanability, brushing was performed for 2 hours with an electric toothbrush manufactured from electric toothbrush bristles. The brush width was measured, and the percentage of the brush width relative to the brush width before the electric toothbrush test was calculated using the following formula (1). Measurements were taken with n=5, and the average value was judged according to the following criteria.
[0038] Hair spread rate (%) = 100 × (ba) / a ... (1) Here, 'a' represents the width of the bristle area of the toothbrush before brushing (mm), and 'b' represents the width of the bristle area of the toothbrush after brushing (mm).
[0039] ◎; Hair opening rate is less than 20.0% ○; Hair separation rate (%) is 20.0% or more and less than 30.0% △; Hair separation rate (%) is 30.0% or more and less than 40.0% ×; The hair separation rate is 40.0% or more but less than 50.0%.
[0040] [Example 1] A mixture of PBT pellets (Toray Industries, Inc., Toraycon 1200S) and 30% by mass of barium sulfate powder with an average particle size of 0.6 μm was supplied to a spinning machine. After melt-kneading in the melt spinning machine, the molten material was extruded from the die. Subsequently, it was cooled and solidified in a cooling bath, then stretched and heat-set to produce monofilaments. After alkali treatment, a tapered shape was created at the tip to obtain brush bristles. Each evaluation was performed and the results are shown in Table 1.
[0041] [Example 2] Brush bristles were obtained in the same manner as in Example 1, except that the mixture was a blend of 10% by mass of barium sulfate powder. Each evaluation was performed and the results are shown in Table 1.
[0042] [Example 3] Brush bristles were obtained in the same manner as in Example 1, except that the mixture was a blend of 50% by mass of barium sulfate powder. Each evaluation was performed and the results are shown in Table 1.
[0043] [Example 4] Brush bristles were obtained in the same manner as in Example 1, except that the mixture was a blend of barium sulfate powder with an average particle size of 2.0 μm. Each evaluation was performed and the results are shown in Table 1.
[0044] [Example 5] Brush bristles were obtained in the same manner as in Example 1, except that the mixture was a blend of barium sulfate powder with an average particle size of 5.0 μm. Each evaluation was performed and the results are shown in Table 1.
[0045] [Example 6] Brush bristles were obtained using the same method as in Example 1, except that polyamide 6·10 pellets (M2001, manufactured by Toray Industries, Inc.) were used. Each evaluation was performed and the results are shown in Table 1.
[0046] [Example 7] Brush bristles were obtained using the same method as in Example 1, except that PTT pellets (SORONA, manufactured by Covation Biomaterials) were used. Each evaluation was performed and the results are shown in Table 1.
[0047] [Comparative Example 1] Brush bristles were obtained using the same method as in Example 1, except that inorganic particles were not added to the resin. Each evaluation was performed and the results are shown in Table 1.
[0048] [Comparative Example 2] Brush bristles were obtained in the same manner as in Example 1, except that the mixture was a blend of 70% by mass of barium sulfate powder. Each evaluation was performed and the results are shown in Table 1.
[0049] [Comparative Example 3] A brush bristle material was obtained using polyamide 6·10 pellets (M2001, manufactured by Toray Industries, Inc.) in the same manner as in Example 1, except that inorganic particles were not added to the resin. Each evaluation was performed and the results are shown in Table 1.
[0050] [Comparative Example 4] Brush bristles were obtained in the same manner as in Example 1, except that the core component was a mixture of PBT pellets (Toray Industries, Inc., Toraycon 1200S) blended with 33.6% by mass of barium sulfate powder, and the sheath component was PBT pellets (Toray Industries, Inc., 1200S), resulting in a core-sheath structure (core component 25% / sheath component 75%). Each evaluation was performed and the results are shown in Table 1. Note that the inorganic particle amount in the table refers to the amount of inorganic particles in the core component.
[0051] [Table 1]
[0052] As is clear from the results shown in Table 1, the brush bristles of the present invention (Examples 1-7) exhibit excellent cleaning properties and high durability during long-term use, achieved by adding an appropriate amount of inorganic particles of suitable particle size.
[0053] In contrast, brush bristles that do not meet the conditions of the present invention (Comparative Examples 1-4) cannot fully exhibit the effects of the present invention. For example, brush bristles without added inorganic particles (Comparative Examples 1 and 3) have low specific gravity and fineness, and cannot maintain cleaning performance. Furthermore, brush bristles with a large amount of added inorganic particles (Comparative Example 2) and brush bristles with a core-sheath structure (Comparative Example 4) have poor durability. [Industrial applicability]
[0054] The brush bristles of the present invention can efficiently transmit applied stress to the bristle tips, resulting in a brush with high plaque removal capabilities and resistance to breakage, thus achieving high durability. Furthermore, the brush bristles of the present invention are suitable for use in toothbrushes, electric toothbrushes, and ultrasonic toothbrushes.
Claims
1. Toothbrush bristles made of monofilaments having a specific gravity of 1.40 to 2.03, a fineness of 350 dtex to 470 dtex, and a bending recovery rate of 45% or more.
2. The toothbrush bristle material according to claim 1, wherein the monofilament is a thermoplastic resin containing 10% by mass or more and 50% by mass or less of inorganic particles.
3. The toothbrush bristle material according to claim 1 or 2, wherein the thermoplastic resin is a polyester resin or a polyamide resin.
4. The toothbrush bristle material according to claim 1 or 2, wherein the inorganic particles are inorganic particles with a mass-average particle size of 5 μm or less.
5. A toothbrush using at least a portion of the toothbrush bristles described in claim 1 or 2.
Citation Information
Patent Citations
Toothbrush
JP1994141923A
High-specific gravity conjugate fiber
JP2000265332A
Toothbrush
JP2001169828A
Method for manufacturing brush bristles, and brush bristles and brush products
JP4807760B2